Mechanism of covalent adduct formation of aucubin to proteins - Kim, DH; Kim, BR; Kim, JY; Jeong, YC (ELSEVIER SCI IRELAND LTD, 2000)
The iridoid glucoside aucubin can irreversibly bind to proteins through the formation of its aglycone. In view of a possible involvement of these protein adducts in the toxicity of aucubin, we investigated the mechanism of binding of aucubin to proteins. [H-3]aucubin in itself did not result in binding to protein whereas it covalently bound to rat serum albumin as a function of exposure time and dose in the presence of beta-glucosidase. The rate and extent of protein binding were significantly increased in the presence of the imine-trapping agent sodium cyanide. Oral administration of [H-3]aucubin to rats showed that the total radioactivity in plasma remained at a similar level for up to 6 h once peak level was reached, suggesting that a considerable amount of radioactivity might be covalently associated with plasma proteins. The levels of radioactivity in the liver and kidney after oral dosing were higher than those after i.v. dosing. These results indicate that the open-chain aglycone of aucubin can form an imine bond with a nucleophilic site of the protein and these irreversible bindings may partially contribute to its biological and toxic effects. (C) 2000 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: BETA-GLUCOSIDASE ACTIVITY; ANTIMICROBIAL ACTIVITY; INVIVO; AGLYCONE; INVITRO; BINDING; RATS